FRI0502 SEASONAL CLUSTERING OF ACUTE SARCOIDOSIS IN GERMANY AND ASSOCIATIONS WITH AIR POLLUTION. (13th June 2020) - Rustler, P.; Schindler, D.; Voll, R.; Kollert, F.
Abstract : Background: Sarcoidosis is a multisystemic granulomatous disorder of unknown origin. The central role of macrophages and granuloma formation, the predominant involvement of lung and skin, and certain risk populations (e.g. firefighters 1, 2 ) might be explained by causative airborne antigen(s) 3 . Whether air pollution is involved in pathogenesis and seasonal clustering of sarcoidosis is uncertain. Objectives: This study has been set to analyze seasonal clustering of acute sarcoidosis and associations to air pollution. Methods: Patients with acute sarcoidosis, defined by bihilar lymphadenopathy, ankle swelling, and/or erythema nodosum plus physician's diagnosis, were included in this retrospective study. Disease onset (seasonal clustering) and associations to air pollution (particulate matter (PM10 ) and nitrogen dixoide (NO2 )) were analyzed. Google Trends queries were conducted to address seasonal clustering on a global scale. Results: A total of 185 patients with acute sarcoidosis were included; 48.7 % of the enrolled patients were female and Löfgren triad was complete in 73.5 % of patients. Acute sarcoidosis clustered from December to June in West Germany (p<0.005, Kendall τ=-0.68), peaking in January (17.8 % of cases) and in the first third of the year (54.5 %). Mean PM10 values clustered from December to April with values between 15 and 40 µg/m 3 . NO2 levels were measured highest from November to March (45 µg/m 3 ) and lowest between April and August (25 µg/m 3 ). Elevated air pollution markers (PM10 and NO2 ) were associated with higher monthly incidence rates of acute sarcoidosis (Cross correlation coefficient ranging between 0.7 -0.8). Google Trends analysis yielded seasonal clustering (p<0.005, Kendall τ = -0.64) in winter and spring months on the northern hemisphere. Conclusion: In Central Europe acute sarcoidosis peaks in winter and spring months (December until March) shortly after PM10 and NO2 maxima are reached. Whether components of particulate matter might be involved in the pathogenesis of sarcoidosis has to be elucidated by further studies. References: [1] Prezant DJ, Dhala A, Goldstein A, Janus D, Ortiz F, Aldrich TK, et al. The incidence, prevalence, and severity of sarcoidosis in New York City firefighters. Chest. 1999; [2] Webber MP, Yip J, Zeig-Owens R, Moir W, Ungprasert P, Crowson CS, et al. Post-9/11 sarcoidosis in WTC-exposed firefighters and emergency medical service workers. Respir Med [Internet]. 2017;132:232–7. [3] Newman LS, Rose CS, Bresnitz EA, Rossman MD, Barnard J, Frederick M, et al. A case control etiologic study of sarcoidosis: Environmental and occupational risk factors. Am J Respir Crit Care Med. 2004;170(12):1324–30. Disclosure of Interests: Philipp Rustler: None declared, Dirk Schindler: None declared, Reinhard Voll: None declared, Florian Kollert Employee of: Novartis